Three new species of the leafhopper genus Oncopsis Burmeister, 1838 (Hemiptera: Cicadellidae, Macropsinae) from Sichuan Province of Southwestern China - Li, Hu; Dai, Ren-Huai; Li, Zi-Zhong (Entomologica Fennica, 2018)
Three new species of the leafhopper genus Oncopsis: O. graciaedeagus sp. n., O. hailuogouensis sp. n. and O. ludingensis sp. n., from Sichuan Province, Southwestern China are described and illustrated in the current paper along with amap showing the type locality (Hailuogou) of these new species in Sichuan Province, China.